2022
DOI: 10.1177/10732748211072976
|View full text |Cite
|
Sign up to set email alerts
|

Models for Predicting Early Death in Patients With Stage IV Esophageal Cancer: A Surveillance, Epidemiology, and End Results–Based Cohort Study

Abstract: Background Despite enormous progress in the stage IV esophageal cancer (EC) treatment, some patients experience early death after diagnosis. This study aimed to identify the early death risk factors and construct models for predicting early death in stage IV EC patients. Methods Stage IV EC patients diagnosed between 2010 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) database were selected. Early death was defined as death within 3 months of diagnosis, with or without therapy. Early death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Similar to the findings in previous studies, female had a better OS in EC patients receiving nCT. Shi et al found that tumor pathologic stage is an early death of patients with stage IV esophageal independent risk factors ( 25 ). This study indicated that EC patients receiving nCT with higher pathologic stage had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in previous studies, female had a better OS in EC patients receiving nCT. Shi et al found that tumor pathologic stage is an early death of patients with stage IV esophageal independent risk factors ( 25 ). This study indicated that EC patients receiving nCT with higher pathologic stage had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that elderly patients has a higher incidence of comorbidities, which may result higher risk of cardiovascular events, but the specific mechanism still needs further analysis. In addition, multivariate competitive risk analysis suggested that EC patients with poorly and undifferentiated (HR: 0.843; 95% CI: 0.757-0.938) and distant tumor stage (HR: 0.315; 95% CI: 0.271-0.366) has lower risk of CVD related death, low degree of differentiation and distant stage are adverse prognostic factors of EC patients (27,28), since the proportion of CVD related death increased with the increase in years of diagnosis, leading to the possibility that these patients may not have a long enough life expectancy to died from CVD. Married patients showed a lower tendency to died from CVD than unmarried patients (HR: 0.883; 95% CI: 0.797-0.978), they often receive more physical and emotional care, encouragement and support than unmarried patients (29), that could be one of the reason.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, predictive factors associated with early mortality in malignant tumors such as breast, liver, nasopharyngeal, esophageal, and gastric cancers have been reported. [10][11][12][13][14]19] However, there are fewer studies on early mortality in elderly SCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, early death (defined as death occurring within 3 months after initial diagnosis) of cancer patients is a very objective clinical feature revealing the aggressiveness of cancer. Researchers have reported predictive factors associated with early death in malignancies such as breast, liver, nasopharyngeal, esophageal, and gastric cancers, [10][11][12][13][14] however, risk factors for early death in elderly SCLC patients remain unreported.…”
Section: Introductionmentioning
confidence: 99%